205 Minimally invasive approaches in locally advanced cervical cancer patients undergoing radical surgery after chemoradiotherapy: a propensity score analysis. (13th November 2020) - Gallotta, V; Federico, A; Fanfani, F; Chiantera, V; Cosentino, F; Turco, L; Legge, F; Pedone Anchora, L; Bizzarri, N; Macchia, G; Valentini, V; Scambia, G; et al.
Abstract : Objectives: To evaluate the oncological and surgical outcome of minimally invasive radical surgery (MI-RS) compared to open radical surgery (O-RS) in locally advanced cervical cancer (LACC) after preoperative chemoradiation (CT/RT). Methods: Data relative to stage IB2-IVA cervical cancer patients managed by CT/RT and RS were retrospectively analyzed. Results: Starting from 686 patients, the propensity score matching resulted in 462 cases (231 per group), balanced for FIGO stage, lymph node status, histotype, tumor grade and clinical response to CT/RT. Overall, 107 recurrences were registered with no difference in the pattern of recurrences between the two surgical approaches. The 5-year disease-free survival (DFS) was 73.7% in the O-RS patients, 73.0% in the MI-RS ones (HR 1.034, 95% CI: 0.708–1.512, p=0.861). The 5-year locoregional recurrence rate was 12.5% (O-RS) versus 15.2% (MI-RS) (HR 1.174, 95% CI: 0.656–2.104, p=0.588). Deaths of disease were 62; the 5-yr disease-specific survival (DSS) was 80.4% in O-RS patients, 85.3% in the MI-RS group (HR 0.731, 95% CI: 0.438–1.220, p=0.228). Estimated blood loss was lower in the MI-RS group (p<0.001), as well as length of hospital stay (p<0.001). Early postoperative complications occurred in 77 (33.3%) patients in the O-RS group, 88 (38.1%) patients in the MI-RS group (p=0.331). Fifty-six (24.2%) patients experienced late postoperative complications in the O-RS group, 61 (26.4%) in the MI-RS group (p=0.668). Conclusion: MI-RS and O-RS are associated with similar rate of recurrence and death from disease in LACC patients managed by surgery after CT/RT. No difference in early and late complications were reported.